An investigation into the role of women in the spatial planning and development of their settlements that are under the custodianship of traditional leaders: A case study of Cala in Sakhisizwe Municipality, Eastern Cape - Sigwela, Noziphiwo Margaret (School of Architecture, Planning and Geomatics, 2024)
This study aims to unpack the planning strategies employed by women who live on communal lands in the rural regions of the Eastern Cape. In South Africa, traditional leaders are the custodians of communal lands. Their patriarchal nature tends to negate gender equalities as envisaged and prescribed in the Constitution of the Republic of South Africa through the Bill of Rights. As a result of this patriarchal nature, women find themselves having to navigate spaces which are embedded with customary laws that continue to uplift the status of men over women. The study investigates how women in communal areas access land, deal with social and economic vulnerabilities and, most of all, how they add their voices to the planning and public decision making processes of their communities. Unequal gender relations and structural inequalities are brought to light by means of the research findings presented in this dissertation. Women's involvement public decision making processes is studied in other academic fields, including in politics, anthropology and sociology. However, such studies are not as extensively in the planning field, specifically with respect to planning in rural areas. Planning in South Africa is understood as a study that tends, more often than not, to focus on cities rather than on rural contexts (as research findings demonstrate). The research method employed in this study is the case study research method, and Cala, which is located on communal lands and which falls within the political jurisdiction of the Sakhisizwe Local Municipality, is the case under study. An in depth investigation of the following themes (in turn, resulted in the establishment of subsidiary research questions) is presented in the subsequent chapters: feminism and black feminism; the South African Constitution; the Traditional Authority Act; the Spatial Planning and Land Use Management Act; communal lands; and lessons from Kenya and Tanzania. Research findings demonstrate a mismatch between the legislation and everyday practices found in Cala. Women are still finding it difficult to navigate traditional spaces. They do not have enough representation in planning and public decision making structures, and, as a result, they remain disadvantaged. In response, planning policy recommendations are presented in the final chapter